Inscriptions on a pillar of the Mandapa - Temples of India Project Team (Jio Institute, 2024)
The pillars of the mandapa (pillared hall) of the Sitaleshwar Temple reveal the presence of a few inscriptions. One of the inscriptions found in the mandapa is a small inscription of two lines.